SOLID WASTE: PERCEPTIONS OF ELEMENTARY SCHOOL STUDENTS - Stangherlin, Caren Cristiane de Castro; Specht, Suzimary (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study aims to estimulate students from nine to eleven years old throught environmental education activities, to understand the importance on reflecting and acting sustainably in favor of environment, specially about the issue of solid residues. The environmental education activities were realized in two groups, the 4th and 5th class at Escola Estadual Bom Conselho, in Silveira Martins city, Rio Grande do Sul state, which the discussed topics were: solid and organic residue, residues separation, composting, reutilization and recycling, remembering the importance of the scavengers of solid residues. The activities instigated students to realize the importance of rethink about their residues and the way they discard it, and the necessity on giving an appropriate and sustainable final destination for the solids residues.